Cooperation effects of radiation and ferroptosis on tumor suppression and radiation injury - Su, Jing; Bian, Chenbin; Zheng, Zhuangzhuang; Wang, Huanhuan; Meng, Lingbin; Xin, Ying; Jiang, Xin (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis is a kind of oxidative stress-dependent cell death characterized by iron accumulation and lipid peroxidation. It can work in conjunction with radiation to increase reactive oxygen species (ROS) generation and disrupt the antioxidant system, suppressing tumor progression. Radiation can induce ferroptosis by creating ROS, depleting glutathione, activating genes linked to DNA damage and increasing the expression of acyl-CoA synthetase long-chain family member 4 (ACSL4) in tumor cells. Furthermore, ferroptosis can enhance radiosensitivity by causing an iron overload, destruction of the antioxidant system, and lipid peroxidation. Radiation can also cause ferroptosis in normal cells, resulting in radiation injury. The role of ferroptosis in radiation-induced lung, intestinal, skin, and hematological injuries have been studied. In this review, we summarize the potential mechanisms linking ferroptosis, oxidative stress and radiation; analyze the function of ferroptosis in tumor suppression and radiation injury; and discuss the potential of ferroptosis regulation to improve radiotherapy efficacy and reduce adverse effects.